Shear behaviour of the UHPC-NSC interface with castellated keys: Effects of castellated key dimension and dowel rebar. (June 2021) - Guan, Dongzhi; Liu, Jiabin; Jiang, Cheng; Chen, Zixuan; Guo, Zhengxing
Abstract: When utilizing ultra-high performance concrete (UHPC) and normal strength concrete (NSC) together, the interface between the UHPC and NSC in this composite structural member is essential and needs to be clearly understood. In this paper, push-off tests are carried out on 10 UHPC-NSC joint specimens with considerations of the castellated key size and the use of dowel rebar. The effect of the cohesion between the UHPC and NSC on the interfacial shear resistance is found to be very limited and can be ignored. The UHPC-NSC joints with castellated keys of 10 mm have the best mechanical performance if no dowel rebar is applied. When there is dowel rebar in the joint specimens, the specimens have shear resistance with post-peak residual loads. The dowel rebar configured specimens with larger castellated keys have higher residual shear resistances because of the improved post-peak residual interlocking effect.